2020
DOI: 10.1186/s12929-020-00655-w
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine methyltransferase METTL3 affects the phenotype of cerebral arteriovenous malformation via modulating Notch signaling pathway

Abstract: Background: Cerebral arteriovenous malformation (AVM) is a serious life-threatening congenital cerebrovascular disease. Specific anatomical features, such as nidus size, location, and venous drainage, have been validated to affect treatment outcomes. Until recently, molecular biomarkers and corresponding molecular mechanism related to anatomical features and treatment outcomes remain unknown. Methods: RNA N6-methyladenosine (m 6 A) Methyltransferase METTL3 was identified as a differentially expressed gene in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“… Si et al (2020) found that METTL3-mediated miRNA m6A methylation promotes stress granule formation and reduces the apoptosis of injury neurons in the early stage of acute IS. Furthermore, Wang et al (2020a , b) found that the expression levels of METTL3 and WTAP were reduced in the larger pathological tissue of cerebral AVMs. Mechanistically, the lack of METTL3 reduced the level of heterodimeric Notch E3 ubiquitin ligase, thereby continuously activating the Notch signaling pathway, which affects the angiogenesis of endothelial cells.…”
Section: Discussionmentioning
confidence: 98%
“… Si et al (2020) found that METTL3-mediated miRNA m6A methylation promotes stress granule formation and reduces the apoptosis of injury neurons in the early stage of acute IS. Furthermore, Wang et al (2020a , b) found that the expression levels of METTL3 and WTAP were reduced in the larger pathological tissue of cerebral AVMs. Mechanistically, the lack of METTL3 reduced the level of heterodimeric Notch E3 ubiquitin ligase, thereby continuously activating the Notch signaling pathway, which affects the angiogenesis of endothelial cells.…”
Section: Discussionmentioning
confidence: 98%
“…105 An inverse correlation was also observed between METTL3 expression and the nidus size of cerebral AVMs. 106 Notch pathway regulator DTX3L was implicated in AVM formation, and in METTL3-deficient endothelial cells, DTX3L mRNA was observed to be hypomethylated and silenced, indicating that m 6 A is crucial for its stability. 106 Furthermore, m 6 A SNP in IRF6 transcript correlated with intracerebral hemorrhage in humans.…”
Section: The Role Of M6a Methylation In Brain Diseasesmentioning
confidence: 99%
“…106 Notch pathway regulator DTX3L was implicated in AVM formation, and in METTL3-deficient endothelial cells, DTX3L mRNA was observed to be hypomethylated and silenced, indicating that m 6 A is crucial for its stability. 106 Furthermore, m 6 A SNP in IRF6 transcript correlated with intracerebral hemorrhage in humans. 101 Collectively, these studies indicate the role of m 6 A methylation in stroke incidence and post-stroke brain damage.…”
Section: The Role Of M6a Methylation In Brain Diseasesmentioning
confidence: 99%
“…When the classic Spetzler-Martin (SM) grading system [17], supplementary scale [18], and even with evolving fMRI-based HDVL grading scale combined with lesion-to eloquence distance (LED) are added [19], the evaluation becomes accurate but tedious at the same time. And there are some objectively advanced biomarkers, such as S100B, matrix metalloproteinase-9 (MMP-9), interleukin-1 beta (IL-1β), vascular endothelial growth factor (VEGF), and N6-methyladenosine methyltransferase 3 (METTL3) [12,[20][21][22], which were proposed to be the predictors for the in-hospital complications and neurological outcomes. However, these indicators were unable to directly provide guidance for clinical practice.…”
Section: Discussionmentioning
confidence: 99%